ANALYZING THE INFLUENCE OF PSYCHOLOGICAL FACTORS ON IMPULSIVE BUYING OF APPAREL CUSTOMERS DURING FACEBOOK LIVE STREAM (CASE STUDY: KLONTONG MANADO ONLINE SHOP SULAWESI UTARA) - Keren Gloria Sondakh; David Paul Elia Saerang; Shinta J. C. Wangke (Universitas Sam Ratulangi, 2023)
The purpose of this study is to analyze the influence of psychological factors on impulsive buying behavior of apparel customers during Facebook live streams, with a case study of the Klontong Manado Online Shop in Sulawesi Utara. The study examines the psychological factors that may lead to impulsive buying behavior, such as Motivation, Attitude, Learning and Perception. This research uses Quantitative Approach with 96 from apparel customers who have participated in the Facebook live streams of Klontong Manado Online Shop. The study found that motivation, attitude, and learning do not significantly influence impulsive buying, while perception has a highly positive and significant effect on impulse purchases of clothes during live streaming on the